Mineral-Induced Enantioenrichment of Tartaric Acid - Gherase, Dragos; Hazen, Robert M.; Krishnamurthy, Ramanarayanan; Blackmond, Donna G. (Synlett, 2017)
Interaction of mixtures of d- and l-tartrates with dissolved gibbsite minerals produces homochiral and heterochiral dimers in a stochastic manner, providing a mechanism for enantioenrichment given a small initial imbalance. This work offers the first suggestion for a path towards the emergence of homochirality in prebiotic metabolism via the glyoxylate scenario.
Keywords: enantioenrichment; prebiotic chemistry; nonlinear effects in enantiomerice excess